Are academic independent directors punished more severely when they engage in violations? - Yi Quan; Sihai Li (China Journal of Accounting Research, 2017)
We use a sample of Chinese A-share listed companies from 2003 to 2013 to explore the reputation damage and overflow effect of academic independent directors who have received supervisory punishment. We find that when companies violate information disclosure rules, the market punishes academic independent directors more severely than nonacademic independent directors for these violations. Furthermore, companies employing punished academic directors face greater declines in their stock price than companies employing punished nonacademic independent directors during a relatively short window before or after the punishment is announced. The punishment of academic independent directors influences the employment of other scholars in the same field and results in a negative overflow effect. This study provides evidence of the market's differential reactions to independent directors with different backgrounds; the findings reflect the double-edged sword of one individual's reputation on organizations.
Keywords: 650; Academic independent directors; Violation behavior; Reputation punishment; Overflow effect